Clinical Implications of Antiviral Resistance in Influenza - Li, Timothy C. M. (Viruses, 2015)
Influenza is a major cause of severe respiratory infections leading to excessive hospitalizations and deaths globally; annual epidemics, pandemics, and sporadic/endemic avian virus infections occur as a result of rapid, continuous evolution of influenza viruses. Emergence of antiviral resistance is of great clinical and public health concern. Currently available antiviral treatments include four neuraminidase inhibitors (oseltamivir, zanamivir, peramivir, laninamivir), M2-inibitors (amantadine, rimantadine), and a polymerase inhibitor (favipiravir). In this review, we focus on resistance issues related to the use of neuraminidase inhibitors (NAIs). Data on primary resistance, as well as secondary resistance related to NAI exposure will be presented. Their clinical implications, detection, and novel therapeutic options undergoing clinical trials are discussed.